APPLICATION OF CONTENT ANALYSIS IN PEDAGOGICAL RESEARCH AND PRACTICE (Annual of the Faculty of Philosophy in Skopje, 2021)
Content analysis is one of the oldest research and most used techniques in social research and pedagogy, with invaluable significance and contribution to the development of educational science and pedagogical practice. At the beginning of its use, this technique had mainly a quantitative character, and later it was developed as a qualitative research technique that aims to reveal the hidden, symbolic meanings of the content in a certain context.In its contemporary meaning and form, content analysis has great potential in studying the pedagogical phenomena, but also for application in the daily educational work in school and extracurricular activities.In the particular research, the content analysis is applied in the instruction of the teaching subject Macedonian language in the initial two educational cycles of primary education. The subject of analysis is the readings recommended with the subject curriculum, which includes readings written by domestic and foreign authors with different genres and genders.The results contain quantitative indicators about the presence of certain types of reading works and qualitative analysis in reference to the reading content, educational and emotional potentials, and ethical impact on students.